If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9+3x=-x+15
We move all terms to the left:
-9+3x-(-x+15)=0
We add all the numbers together, and all the variables
3x-(-1x+15)-9=0
We get rid of parentheses
3x+1x-15-9=0
We add all the numbers together, and all the variables
4x-24=0
We move all terms containing x to the left, all other terms to the right
4x=24
x=24/4
x=6
| -7u+3(u-2)=10 | | 7/3=x/84 | | 26=4(v+3)-2v | | 3x=7/84 | | 2.5x/(.01x)=1600 | | 6=-6y+3(y-4) | | 1.5/6=x/7 | | 66-y=247 | | 35-10x=0 | | 6k+8=-2k-24 | | 145=245-y | | 90=-y+181 | | 6(a+4)=3a-12 | | 2a+5=40 | | (700*(2x))+(194*x)=503000 | | 72x+6=1 | | √72x+6=1 | | 64x-2=42x-1= | | 15x+10=235 | | 9m2+7=0 | | 7x-4=3x+23=9x-6 | | 3p=24-p | | 25f2-25=0 | | 0=-t^2+9t+52 | | 8x-10=9x-38 | | 8x-10=9x-33 | | x+8+2x+5+3x+10=86-x | | 3m-m+1=6m | | 3(5x+4)–6=11x–2 | | 9-3x=x+15 | | 6m-m+1=3m | | 5(x+4=3(x+10)-8 |